Determination of corticosteroids in Malay traditional jamu using RP-HPLC-PDA method - Yet, Lew Chin (2023)
Corticosteroid is a common adulterant found in herbal medicines which may bring adverse effectson health. In Malaysia, thereare reported cases highlighted the presence of corticosteroids in Jamu preparations. The aim of this study was to evaluate the sensitivity and effectiveness of a high-performance liquid chromatography (HPLC) technique for the identification and quantification of prednisolone, hydrocortisone, and dexamethasone in conventional Jamupreparations produced in Malaysia. The study thoroughly examined samples from local Jamumarkets in Kelantan and online retail platforms like Lazada and Shopee to detect specific corticosteroids.The RP-HPLC-PDA system was utilized to detect and quantify the analytes, namelyprednisolone, hydrocortisone, and dexamethasone. The linearity of the calibration curve in detecting the selected steroids achieved an r2value of 0.999, 0.993, and 0.951, respectively. One of the analyzed samples wasfound to contain hydrocortisonewith concentration of 0.08mg –0.10 mg per capsule(%RSD = 0.19 -10.17%for repeatability test;12.14% for reproducibility test). The detection limit (LOD) for prednisolone and hydrocortisone is 1 ppm, while for 0.1 ppm for dexamethasone. For the quantification limit (LOQ), it is 3 ppm for prednisolone and hydrocortisone, and 0.4 ppm for dexamethasone. Theaccuracyof the results is indicated by the percent recovery values, which are 45%, 65%, and 75% respectively for prednisolone, hydrocortisone, anddexamethasone.The validated method is deemed to be suitable in determining corticosteroids in Jamuproducts.